2022
DOI: 10.3390/cells11071158
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Early-Pregnancy Mechanisms: Mast Cells and Chymase CMA1 Shape the Phenotype and Modulate the Functionality of Human Trophoblast Cells, Vascular Smooth-Muscle Cells and Endothelial Cells

Abstract: Spiral-artery (SA) remodeling is a fundamental process during pregnancy that involves the action of cells of the initial vessel, such as vascular smooth-muscle cells (VSMCs) and endothelial cells, but also maternal immune cells and fetal extravillous trophoblast cells (EVTs). Mast cells (MCs), and specifically chymase-expressing cells, have been identified as key to a sufficient SA-remodeling process in vivo. However, the mechanisms are still unclear. The purpose of this study is to evaluate the effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Color Doppler ultrasound can neither detect the low-speed blood flow inside the placenta villi space nor identify the individual villi blood vessels [ 13 ]. Several large cohort studies have also indicated that conventional ultrasound changes are associated with low sensitivity and specificity in the FGR population [ 14 ]. FGR is mostly caused by placental dysfunction secondary to uterine-placental-fetal blood circulation disorders, and early diagnosis is of great significance for its treatment and prognosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler ultrasound can neither detect the low-speed blood flow inside the placenta villi space nor identify the individual villi blood vessels [ 13 ]. Several large cohort studies have also indicated that conventional ultrasound changes are associated with low sensitivity and specificity in the FGR population [ 14 ]. FGR is mostly caused by placental dysfunction secondary to uterine-placental-fetal blood circulation disorders, and early diagnosis is of great significance for its treatment and prognosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesized that these cell populations could be responsible for the exacerbated immune response and tissue damage that occurs in the placenta during infection with the high-virulence isolate as has also been suggested for infections at early gestation (15,21,68). On the other hand, it is known that mediators from mast cells were also increased in the Nc-Spain7infected heifers, playing a key role in inflammation and in the pathogenesis of other protozoan parasitic disease (73,74), but to our knowledge, there are no studies about its importance in bovine neosporosis, and this issue should be investigated since there are some studies in humans that relate these cells to pregnancy disorders (56,75). In addition, as described for T. gondii and N. caninum, some of these immune populations can be hijacked by the parasite, which can use them as a Trojan horse to spread systemically, cross biological barriers and reach immune privileged organs (53, 76).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study demonstrated a novel immune evasion mechanism in N. caninum based on the promotion of host mitophagy (56). This mechanism could impair the production of ROS and attenuate the production of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%